2021
DOI: 10.37648/ijrmst.v11i02.003
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis: Review of Treatment Modalities

Abstract: Proficient treatments are accessible for the management of osteoporotic diseases. Antiresorptive remedies, comprising bisphosphonates and denosumab, increment bone mineral density (BMD) and diminish the hazard of breaks by 20–70%. Bonemineralisation or bimodal-efficacy of medication invigorate bone arrangement and increment BMD more than the antiresorptive treatments. A couple of investigations have illustrated that these medicines are preferred over anti-resorptive in avoiding breaks in patients with serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Due to the small sample size, it was noticed in this study that the association between BMI and age is unstable. Moreover, the limitation of the study could be due to variation in the response which is primarily linked to the surrounding milieu (52,53) which modulated cellular behaviour (54,55) based on localized tissue oxygen level (55,56) or or presence of sufficient vitamins and minerals (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small sample size, it was noticed in this study that the association between BMI and age is unstable. Moreover, the limitation of the study could be due to variation in the response which is primarily linked to the surrounding milieu (52,53) which modulated cellular behaviour (54,55) based on localized tissue oxygen level (55,56) or or presence of sufficient vitamins and minerals (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that lisinopril increased the expression of CD34 in bone tissue in a mouse model of osteoporosis. 6 While the exact mechanism by which lisinopril increases CD34 expression in bone tissue is not fully understood, it is thought to be related to the drug's ability to inhibit the ACE enzyme. Inhibition of ACE can lead to an increase in the production of a hormone called angiotensin II, which has been shown to stimulate the production of CD34 in bone tissue.…”
Section: Introductionmentioning
confidence: 99%